2014
DOI: 10.1016/j.jviromet.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Stability of infectious human coronavirus NL63

Abstract: The human coronavirus NL63 was identified in 2004 and subsequent studies showed its worldwide distribution. Infection with this pathogen is associated with upper and lower respiratory tract diseases of mild to moderate severity. Furthermore, HCoV-NL63 is the main cause of croup in children. Within this study an optimal protocol for freeze-drying that allows safe and effective preservation of HCoV-NL63 infectious material was developed. Lyophilized virus preparations can be stored either at ambient temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…90,123,124,134,135 The addition of virus stabilizers can extend the viability. 138 At typical working room temperatures (~20°C-22°C), virus titers decline, but detectable viable virus can last up to 3 to 14 days, or longer with preservatives. 78,80,94,123,133,[137][138][139] Between room temperature and 56°C, progressive viral loss is observed.…”
Section: Temperature Modulationmentioning
confidence: 99%
“…90,123,124,134,135 The addition of virus stabilizers can extend the viability. 138 At typical working room temperatures (~20°C-22°C), virus titers decline, but detectable viable virus can last up to 3 to 14 days, or longer with preservatives. 78,80,94,123,133,[137][138][139] Between room temperature and 56°C, progressive viral loss is observed.…”
Section: Temperature Modulationmentioning
confidence: 99%
“…[40][41][42] It should be noted that many studies have concluded that viruses remain stable through multiple freeze-thaw cycles, thus minimizing sample handling, and aliquoting may be possible before banking samples. [43][44][45][46][47] It is also highly recommended that the electronic records should include documentation that the samples could be potentially infectious, but best practices note that any sample shall be Legal entity or part of a legal entity that performs biobanking, whereas biobanking is defined as process of acquisitioning and storing, together with some or all of the activities related to collection, preparation, preservation, testing, analyzing, and distributing defined biological material, as well as related information and data Hewitt and Watson 3 Biobanks include collections of human, animal, plant, and microbial samples and these collections must be associated with sample data and must be managed according to professional standards 2 SIMEON-DUBACH AND HENDERSON approached as potentially infectious. The World Health Organization has created an extensive technical library online of interim guidance documents to support safety in health care and community settings during the COVID-19 pandemic.…”
Section: Safety Challengesmentioning
confidence: 99%
“…This technique effectively inhibits both biological growth and chemical reactions. It is widely used for creating vaccines and is perhaps the most cost-effective method for stabilizing infectious material (Florek et al 2014 ). The cryoprotectants added during the freezing phase preserve the viral lipid membrane, and consequently, the infectivity of the virus even after the primary and secondary drying steps (Salvucci 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cryoprotectants added during the freezing phase preserve the viral lipid membrane, and consequently, the infectivity of the virus even after the primary and secondary drying steps (Salvucci 2011 ). Indeed, Florek et al ( 2014 ) demonstrated that lyophilized HCoV-NL63, which is responsible for airway infections, remained stable for 2 months at 4 °C and 14 days at room temperature.…”
Section: Resultsmentioning
confidence: 99%